E-Module Development using Kvisoft Flipbook Maker through the Problem Based Learning Model to Increase Learning Motivation - Situmorang, Minar; Yustina, Yustina; Syafii, Wan (Journal of Educational Sciences, 2020)
This study aims to develop e-modules through the Problem Based Learning (PBL) model. The type of this research was development research with the ADDIE model. The trial subjects were students of SMAN 1 Seberida. The research instruments were observation, interview, media expert validation questionnaire, material expert, biology teacher validation, student and student response questionnaire. Qualitative data analysis techniques in the form of qualitative descriptive observations and interviews and presented at the analysis stage, suggestions from media expert validators, materials, biology teachers, student and student responses were carried out descriptively and qualitatively and presented in the development stage. While the score of the biology teacher validation questionnaire was carried out using Descriptive statistics by presenting data through tables. The validation results of media experts, material experts and biology teachers on the e-module were 3.63, 3.62 and 3.71, respectively with valid category. The results of student and student response analysis obtained an average score of 89.98 and 87.7 which are categorized as very practical. Based on these results, it can be concluded that the electronic module with the Kvisoft flipbook maker is suitable for use as learning material and can be tested in direct learning.